Tocilizumab and Systemic Corticosteroids in the Management of Patients with COVID-19: A Systematic Review and Meta-Analysis. (September 2021) - Alkofide, Hadeel; Almohaizeie, Abdullah; Almuhaini, Sara; Alotaibi, Bashayer; Alkharfy, Khalid M.
Highlights: Few studies assessed combining tocilizumab and corticosteroids in treating COVID-19. The combination of tocilizumab and corticosteroid was compared here to standard care. Combining tocilizumab and corticosteroid resulted in lower mortality rates. There is an urgent need for well-designed trials to evaluate this combination. Abstract: Background: To date, there is no effective treatment for the new coronavirus disease (COVID-19). We aimed to systematically review the literature on the association between the combination of tocilizumab (TCZ) and systemic corticosteroid therapy (SCT) on outcomes of COVID-19 patients. Methods: We searched MEDLINE, Cochrane Central, and preprints, for studies in which health outcomes were compared between adults with severe COVID-19 who received TCZ and SCT and those who received standard of care without TCZ. Record screening, data extraction, and risk of bias assessment were performed in duplicate. Random effect models were used when pooling crude numbers and adjusted effect estimates of study outcomes. Results: Our search identified seventeen studies. The pooled crude mortality rate was lower in the combination arm (relative risk, RR=0.62, 95% confidence interval [CI]=0.42 – 0.91; I 2 =60%). The adjusted mortality rates were also lower in the combination arm (RR=0.58, 95% CI=0.42 – 0.81; I 2 =71%). The rate of superinfections did not differ between the two interventions. Conclusions: The findings of this study show that combination of TCZ and SCT compared to SOC has lower mortality rates. There is an urgent need for well-designed randomized trials to assess the safety and efficacy of this combination in subjects with severe COVID-19.